BIOTIC AND ABIOTIC EVENTS IN A SHALLOW CARBONATE PLATFORM (UPPER CRETACEOUS, SOUTH PYRENEAN MARGIN) - Caus, E.; Albrich, S.; Berästegui, X.; Bernaus, J. M.; Boix, C.; Villalonga, R. (Bulletin of the Geological Society of Greece, 2007)
A detailed sedimentological and paleontological study of the Late Santonian-Late Campanian carbonate platform deposits of the Serres Marginals area (South margin of the Pyrenean Basin) has been performed. Three depositional shallow carbonate sequences have been distinguished (CI, C2 and C3). Within the shallow platform sequences moderate energy subtidal to intertidal, high energy sand-shoal, protected lagoon and restricted lagoon to lacustrine fades have been identified.